2022
DOI: 10.1158/1078-0432.ccr-21-2718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Duration of Neoadjuvant Aromatase Inhibitors on Molecular Expression Profiles in Estrogen Receptor–positive Breast Cancers

Abstract: Disclosure declarations: M.C.U.C. has a patent for Breast Cancer Classifier: US Patent No. 9,631,239 with royalties paid, is an advisory member of Veracyte and receives research funding from NanoString Technologies. MD receives honoraria from Myriad Genetics and is a consultant and advisory board member of GTx, Radius Health, Orion Pharma, Lilly, Agile and Astrazeneca, has received funding from Pfizer (Inst) and Radius Health (Inst) and has been payed expenses from Pfizer and Myriad Genetics. HT reports a gran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Noteworthy, Bergamino et al. 30 observed a molecular downstaging under AI presurgical treatment that was consistent with our findings. Interestingly, a shift towards less aggressive subtypes and ROR score was also observed in the SOLTI-CORALEEN trial of patients with HR+/HER2-negative disease randomized to receive NACT or NET+CDK4/6-inhibitor ribociclib.…”
Section: Discussionsupporting
confidence: 93%
“…Noteworthy, Bergamino et al. 30 observed a molecular downstaging under AI presurgical treatment that was consistent with our findings. Interestingly, a shift towards less aggressive subtypes and ROR score was also observed in the SOLTI-CORALEEN trial of patients with HR+/HER2-negative disease randomized to receive NACT or NET+CDK4/6-inhibitor ribociclib.…”
Section: Discussionsupporting
confidence: 93%
“…In that same analysis, we observed an encouraging trend towards better survival outcomes associated to such a molecular downstaging 16 . Notably, Bergamino M. et al observed a consistent molecular downstaging under AI presurgical treatment, as well 29 . A shift towards less aggressive subtypes and ROR score was also observed in the SOLTI-CORALEEN trial of patients with HR+/HER2-negative disease randomized to receive NACT or NET+CDK4/6-inhibitor ribociclib 30 .…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, Bergamino M. et al also observed significant changes in the expression of immune response/immune-checkpoint components' genes, that were associated with AIresistant tumors 29 . In our cohort, although with a limited number of immune-related genes, namely CD4, CD8A, PDCD1 (PD1) and CD274 (PD-L1), we also observed a significant upregulation, with no differences between HER2-0 and HER2-low disease.…”
Section: Discussionmentioning
confidence: 98%
“…PD1, PD-L1 genes) with both NACT and standard NET emerged. Bergamino et al had previously observed the induction of immune in ltration with a short course of preoperatory aromatase inhibitors [32]. Additionally, the increase in immune-related therapeutic targets (i.e.…”
Section: Discussionmentioning
confidence: 96%